Evaluation of the doxycycline release from AH26 sealer-doxycycline combination: An ex vivo study - Yazdi, Kazem Ashofteh; Shokouhinejad, Noushin; Moazeni, Esmaeil; Mirzayi Rad, Sina (Iranian Endodontic Journal, 2011)
INTRODUCTION: The purpose of this ex vivo study was to determine the releasing characteristics and doxycycline dentinal diffusion of AH26 sealer-doxycycline combination from apical 3mm of tooth root and apical foramen. MATERIALS & METHODS: One-hundred and two recently extracted single-rooted human teeth were decoronated and prepared with #3 and #4 Gates-Glidden drills and rotary Mtwo files. Smear layer was removed; all surfaces except for apical 3mm of each root were sealed with two coats of nail polish. To quantify the release and diffusion of the doxycycline at different time intervals (30 min, 48 and 72 h) after root canal obturation, the samples were randomly divided into three groups (n=30; 0.5 h, 48 h, 72 h). To evaluate the release of doxycycline from AH26 sealer-doxycycline combination at six concentrations of antibiotic including 0.5%, 1%, 2%, 5%, 10% and 20%; each experimental group was divided into six equal subgroups (n=5). Root canals were filled with gutta-percha and AH26-doxycycline combinations and then were placed in vials containing 1.25mL of phosphate buffer saline solution (PBS). After 30 min, 48 and 72 h, the amount of doxycycline released from specimens into PBS were determined by measuring the absorbance values using UV spectrophotometry at λmax=350 nm. Data were analyzed using two-way ANOVA. RESULTS: The findings of this study revealed that AH26 sealer-doxycycline combination released variable measures of antibiotic at each time interval and in the various concentrations. At 30 min, no statistically significant differences were obtained between the results of subgroups, but at 48 and 72 h these differences were significant (P < 0.001). The results also showed that differences between 0.5 h, 48 h and 72 h were significant within subgroups (P < 0.01). CONCLUSION: Under the conditions of this ex vivo study, doxycycline can be released from AH26 sealer-antibiotic combination through 3mm of apical root and apical foramen at 30 min, 48 and 72 h after mixing the sealer with doxycycline at concentrations of 0.5% up to 20%.